Substructure analysis of building frame under lateral loads - Gin, Ng Soe (1978)
This thesis presents the computer analysis to a space building frame subjected to lateral loads. To save computer storage capacity, a substructure approach is adopted in the analysis.
Generally, a structural building frame is a combination of plane frames, shear walls, and columns. In this thesis, the plane frames which are connected at right angles are considered as plane frame substructures, while the shear walls, columns which have significant torsional effects are called the torsional element. When a building is subjected to loads, the plane frame substructures will take account of the shear and bending moment resistances of each structural member, while the torsional elements include the twisting resistances of the vertical members.
The plane frame substructure analysis in the computer program was formerly developed by Dr. Salvador F. Reyes at the UP Computer Center. This thesis serves as an extension with the inclusion of the torsional element analysis to the structural analysis. The research works of this thesis are experimented and implemented in the ECLIPSE C/300 Computer of the Unisystems Group Corporation.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman.
Keywords: Framing (Building) -- Data analysis